User perception: the changes of manual paper to electronic paper as wireless Internet devices in Klang Valley / Jamaliah Mohd Arshad - Mohd Arshad, Jamaliah (2005)
This research looks into the user perception if the changes happen from manual paper to electronic paper. The user also asked their perception about electronic paper as wireless internet devices. Data and information in this study was obtained from interview and questionnaire. The data composed for the study was analyzed using the graph and descriptive statistic. The finding indicate that respondents especially students and worker agree to use electronic paper as wireless internet devices widely in the fiiture. This is the majority result, approxunately 70% from 150 respondents. This study also exposes the advantage and the sophisticated features of eiecfronic paper compare to manual paper. Many benefits will get from the usage of electronic paper according to its special devices. This is usefril for our friture in learning or to do the important work in our life.